Feasibility and Stability of a Kind of Model Predictive Control with Additive Uncertainties (Communications in Mathematical Research, 2021)
In this paper the feasibility and stability of open-loop min-max modelpredictive control (OL-MMMPC) for systems with additive bounded uncertaintiesare considered. It is found that the OL-MMMPC may be infeasible and unstable ifit is initially feasible. A sufficient condition for feasibility and stability of the OL-MMMPC is presented. Then an improved OL-MMMPC algorithm is proposed, whichguarantees the robust stability of the closed-loop system once it is initially feasible.The effectiveness of this algorithm is illustrated by a simulation example.
Keywords: additive bounded uncertainty; predictive control; feasibility; stability.